Spectroscopic and microscopic evidence for adsorption of lipase from Candida rugosa onto calcined layered double hydroxides - Md. Yunus, Noor Mona; Abdul Rahman, Mohd Basyaruddin; Basri, Mahiran; Hussein, Mohd Zobir; Salleh, Abu Bakar; Raja Abdul Rahman, Raja Noor Zaliha (2007)
Lipase from Candida rugosa (CRL) was adsorbed onto three calcined layered double hydroxide (CLDH): Mg/A1-NO3- (CMAN) and Zn/A1-NO3- (CZAN). Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy (SEM-EDX) and protein staining light microscopy analyses were applied to provide direct spectroscopic and microscopic evidence for the adsorption of CRL onto CLDH. SEM-EDX spectra show CRL presence in CMAN-CRL, CNAN-CRL and CZAN-CRL prepared. Blue spots on the surface of CMAN-CRL,CNAN-CRL and CZAN-CRL stained with Coomasie Blue R confirm protein adsorption onto supports. The catalytic activity of all three CLDH-CRL was also evaluated in synthesis of methyl caprylate and results showed that CMAN-CRL and CNAN-CRL exhibited 70% conversion while CZAN-CRL exhibited 80% conversion compared to free lipase that exhibited only 6% conversion only.